2009
DOI: 10.7773/cm.v35i2.1525
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of culturable bacteria from tropical coastal waters

Abstract: In this study we isolated and characterized some culturable bacteria from tropical coastal waters of Peninsular Malaysia. We obtained between 0.23 and 1.85 × 10 3 cfu mL −1 in the Zobell 2216E medium, and cultured 0.04% to 0.12% of total bacterial counts. Different bacterial strains were then selected by 16S rDNA RFLP using four restriction enzymes (DdeI, HhaI, RsaI, and Sau3AI), of which HhaI gave the most RFLP patterns. A total of 54 unique strains were obtained and these were identified by their 16S rDNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…PCR amplication was carried out according to the following conditions: initial denaturation at 94 C for 2 min; 35 cycles of denaturation for 30 s at 94 C, annealing for 40 s at 55 C, extension for 90 s at 72 C; and a nal extension at 72 C for 7 min. PCR products were then puried using the QIAquick® PCR Purication Kit (QIAGEN, Germany) as reported earlier by Lee et al 23 The 16S rDNA sequences of each isolates were compared to GenBank entries using Basic Local Alignment Tool (BLAST) in order to obtain a preliminary affiliation.…”
Section: Identication and Characterization Of Bacteriamentioning
confidence: 99%
“…PCR amplication was carried out according to the following conditions: initial denaturation at 94 C for 2 min; 35 cycles of denaturation for 30 s at 94 C, annealing for 40 s at 55 C, extension for 90 s at 72 C; and a nal extension at 72 C for 7 min. PCR products were then puried using the QIAquick® PCR Purication Kit (QIAGEN, Germany) as reported earlier by Lee et al 23 The 16S rDNA sequences of each isolates were compared to GenBank entries using Basic Local Alignment Tool (BLAST) in order to obtain a preliminary affiliation.…”
Section: Identication and Characterization Of Bacteriamentioning
confidence: 99%
“…For most of the studies considered in this review, the choice of bacteriological parameters used was largely conventional faecal indicator bacteria. Lee et al (2009) reported a study on characterization of culturable bacteria from selected coastal environments along the Straits of Malacca. Using an approach based on 16S rDNA restriction fragment length polymorphism (RFLP), and 16S rDNA sequence analysis, the study determined the bacterial diversity in these coastal waters presenting a comparison analysis of culturable versus unculturable bacteria.…”
Section: Bacteriological Quality Of Coastal Beaches In Malaysiamentioning
confidence: 99%
“…Some autochthonous extremophile strains generate biohydrogen as a substrate to treat organic waste to survive and use the macromolecules present in polluted marine environments as a carbon source (Oguntoyinbo 2007 ; Lee et al 2009 ). In fact, halophytes strains are examples of extremophile microorganisms found in marine environments, with a remarkable ability to withstand harsh conditions and decontaminate the environment.…”
Section: Introductionmentioning
confidence: 99%